Prenatal Detection of Placenta Accreta: A Comparison of Doppler Ultrasound and MRI: Placenta Accreta: Doppler Ultrasound and MRI - Huma, Zill e; Ali, Rana Abid; Naz, Humeera; Afzal, Madiha; Aziz, Uzma; Jan, Sadiq (Pakistan Journal of Health Sciences, 2024)
Placenta accreta is a severe maternal complication where the placenta abnormally attaches to the uterine wall, causing significant maternal and neonatal morbidity. Objectives: To compare the effectiveness of Doppler ultrasound and magnetic resonance imaging in the early detection of placenta accreta and their impact on maternal and fetal outcomes. Methods: Using purposive sampling, 150 high-risk pregnant women were screened with Colour Doppler Ultrasonography and magnetic resonance imaging. Findings were confirmed at delivery. Maternal outcomes included blood transfusion, emergency hysterectomy, intensive care unit admission, and hospital stay. Fetal outcomes included preterm birth, low birth weight, and neonatal intensive care unit, admission. Sensitivity, specificity, positive, and negative predictive values were calculated. Mc-Nemar's test compared modalities. Results: Of 150 patients, 74 had placenta accreta. Colour-Doppler ultrasonography had a sensitivity of 86.5% and specificity of 89.1%, diagnosing 64 cases. Magnetic resonance imaging showed 79.7% sensitivity and 83.3% specificity, identifying 59 cases. Colour-Doppler ultrasonography was linked to fewer emergency hysterectomies (p=0.032) and shorter intensive care unit stays (p=0.045). Preterm birth (p=0.028) and low birth weight (p=0.037) were higher in placenta accreta cases diagnosed with antepartum, though neonatal intensive care unit, admissions did not differ (p=0.451). Magnetic resonance imaging helped in inconclusive Colour-Doppler ultrasonography cases. Conclusions: It was concluded that Colour-Doppler ultrasonography is more effective than magnetic resonance imaging for early Placenta accreta detection, offering better diagnostic accuracy and improved outcomes. The findings highlight its value in the clinical management of high-risk pregnancies.